الأدب السياحي في "رواية الملحد" لعبد الرشيد هميسي - سليماني, ايمان; خوازم, مريم; نصيرة, وئام (جامعة الوادي - University of Eloued, 2023)
تعالج المذكّرة موضوع "الأدب السّياحيّ في رواية الملحد"وارتأينا في هذه الدّراسة إلى البحث عن السّياحة في هذا العمل الأدبيّ الذي حاول الكاتب من خلاله كسر النّمطيّة، وإبراز الجانب السّاحر من فضاء صّحراء حاسي خليفة، لإغراء السّيّاح إلى زيارتها والتّمتّع بمناظرها الخلّابة، والتعرّف على نمط حياة أهلها. وقد اعتمدنا في هذا البحث المنهج الوصفيّ، وكذا القراءة التّحليليّة التي مكّنتنا من الكشف عن جماليّة السّرد الرّوائيّ الجزائريّ السّوفيّ، الذي تميّز بالمزج بين الواقع المتخيّل وبين الإنسان الصّحراويّ وثقافته وأحلامه التي يطمح الوصول إليها على الرّغم من حالة البساطة والبداوة التي يحياها، فجاءت الرّواية مفعمة بالدّلالات الاجتماعيّة والثّقافيّة منها ما تعلّق بالعادات والتّقاليد والتّراثوغيرها من هذه الدّلالاتوالمعاني الخفيّة التي توحي بصعوبة حياة الصّحراء تارة، وجمال العيش فيها والسّفر إليها تارة أخرى . Abstract: The memorandum deals with the topic of “tourist literature in the novel of the atheist.” In this study, we decided to search for tourism in this literary work, through which the writer tried to break stereotypes, highlight the charming side of the Hassi Khalifa desert, to entice tourists to visit it, enjoy its stunning views, and identify the style of the lives of its people. In this research, we adopted the descriptive approach, as well as the analytical reading, which enabled us to reveal the beauty of the Algerian-Soviet novelist’s narrative, which was distinguished by the mixture between the imagined reality and the desert man, his culture, and his dreams that he aspires to reach despite the state of simplicity and nomadism in which he lives. Social and cultural, including those related to customs, traditions, heritage, and other such hidden indications and meanings that suggest the difficulty of desert life at times, and the beauty of living in it and traveling to it at other times.
Keywords: الأدب السّياحيّ، الفضاء الصّحراويّ، العادات والتّقاليد.; tourism literature, desert space, customs and traditions.